Proposed method: mean delays synchronization protocol (MDSP) for wireless sensor networks. Issue 1 (24th January 2020) - Chelik, Mourad; Beghdad, Rachid
Abstract : Purpose: Many synchronization approaches are based on low-level time capturing, causing a tight integration with the Media Access Control (MAC) layer. Alternatively, this study aims to present a hybrid approach combining both receiver–receiver and sender–receiver schemes to reduce the variation of two-way message exchange durations, in heavy-load networks. To achieve network-wide synchronization, a variant of Prim's algorithm (Cormen et al., 2009 ) is used to build a spanning tree, guaranteeing the minimum number of ancestors and limited error propagation. The simulation results show that the proposed approach is very competitive with a set of the most-cited synchronization protocols. In addition, a new synchronization simulator SynSim was developed using C++ language Design/methodology/approach: To achieve network-wide synchronization, a variant of Prim's algorithm (Cormen et al., 2009 ) is used to build a spanning tree, guaranteeing the minimum number of ancestors and limited error propagation. Findings: Simulation results show that the proposed approach is very competitive with a set of the most-cited synchronization protocols. In addition, a new synchronization simulator SynSim was developed using in C++ language. Research limitations/implications: It can be concluded from the experiments that MDSP is suitable for WSNs especially if MAC layer timestamping is not possible. So, the mean delays synchronization protocol (MSDP) is suitable to achieve time synchronization in single-hop and multi-hop networks without the MAC layer timestamping in large wireless sensor network (WSN) deployments. Practical implications: A future enhancement of MDSP could be switching between the traditional timestamping and the new proposed timestamping based on a given threshold, which is the number of nodes in the neighborhood and the load of the network. It will be also interesting to test it in a prototype. The proposed solution can be used in practice to implement the Time-division multiple access (TDMA) protocol in a WSN. In addition, the proposed simulator can be used in a computer network synchronization protocols course. Originality/value: To the best of authors' knowledge, this study's contribution is original. In addition, the authors implemented a new synchronization simulator